Design, synthesis, and biological evaluation of tricyclic pyrones and thiouridine nucleosides - Pokhrel, Laxman (Kansas State University, 2013)
The first chapter in this thesis includes the design, synthesis, and evaluation of anti-Alzheimer and anti-norovirus activities of tricyclic pyrones (TPs). Alzheimer’s disease is a major cause of dementia and sixth leading cause of death; it is a growing problem all over the world. On the other hand, norovirus, a highly contagious agent is responsible for more than 90% of non-bacterial gastroenteritis causing severity mainly in the closed environments. No drugs exist to eradicate the symptoms developed by both of these disorders. Studies have shown that the development of Alzheimer’s disease and the infection of norovirus are dependent on cholesterol metabolism. More specifically, the inhibition of acyl-CoA: cholesterol acyltrasferase (ACAT) led to the reduction of plaques in Alzheimer’s disease as well as reduced the infection of norovirus. Mimicking the structure of CP2, a TP with promising anti-Alzheimer activities, a library of tricyclic pyrones containing phenyl, naphthyl, heterocyclic, and dipeptidyl moieties were synthesized and evaluated for their anti-Alzheimer and anti-norovirus efficacies. Several TPs containing phenyl and naphthyl groups showed sub-micromolar to nanomolar potencies for the protection of neuronal MC65 cells from Aβ-oligomers induced death. Similarly, the TPs containing pyrrolyl, imidazolyl, and quinolinyl moieties were effective to inhibit the norovirus replication in low micromolar range. The most effective TPs from MC65 cells protection assay were also effective in the inhibition ACAT and up-regulation ABCA1 gene. The second chapter in this thesis includes the design, synthesis, and anti-norovirus activity of thiouridine nucleosides. Many nucleosides have demonstrated effective inhibition of viral RNA polymerase, and some are progressing at different level of clinical trials for the treatment of hepatitis C virus. Some of the nucleosides, including 2’-C-methyl and 2’-amino substituted analogs, were found to effectively inhibit the norovirus replication. In the search of more potent anti-noroviral compounds, two thiouridine nucleosides were synthesized and evaluated as anti-norovirus agents. Both of these analogs were ineffective up to 50 μM for the inhibition of norovirus replication in cell based assay. Proposed work of converting these nucleosides to their phosphoramidate derivatives is also described.
Keywords: Organic synthesis; Medicinal chemistry; Chemistry (0485)